The organization of the mental lexicon in late second language learners - Yüksel Aytar, Hanife Emel. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The present study compares the organization of words in the mental lexicon in native and nonnative speakers of English. More specifically, the study explores potential differences in two groups with respect to the extent of reliance on semantic and/or orthographic relations in the mental organization of words. It has been hypothesized that late L2 learners would rely more on orthographic relatedness among words in their lexical organization. Native speakers, however, are predicted to do the mental organization based on the semantic connection. To this aim, first language (L1) Turkish speaking adults who are late second language (L2) learners of English were compared to native speakers of English via a masked priming lexical decision experiment. L2 participants were analyzed in two proficiency groups (low and high) to identify a potential developmental shift in their organization of the mental lexicon. The masked priming task (MPT) measured and compared participants’ accuracy and reaction times (RT) in four prime conditions: i) Identity (prison-PRISON); (ii) Semantically-related (crime-PRISON); (iii) Orthographically-related (priest-PRISON); and (iv) Unrelated (truck-PRISON). The results of the MPT revealed that overall, the low L2 proficiency group was the slowest among the groups. Furthermore, in all groups the following pattern of priming was found: IdentityRT<SemanticRT<OrthographicRT<UnrelatedRT. This tendency suggests that in both native and nonnative groups, the organization of words is based on semantic relatedness rather than orthographic ones. Nevertheless, the lack of statistically significant interaction between primes and groups makes it difficult, at this point, to make a strong claim on the mental organization of words in the lexicon.
Keywords: Second language acquisition -- Study and teaching.; Language acquisition -- Age factors.